Effects of alkali treatment on the bending and fracture behavior of biomaterial bamboo - Xiaohan Chen; Xianke Wang; Shaohua Gu; Aiyue Huang; Haitao Cheng (Polymer Testing)
Although bamboo has broad application prospects in the transportation industry, its insufficient flexibility remains a challenge when designing components with large curvature and complex shapes. In this study, SEM, XRD, FTIR, and micron-level computed tomography (Micro-CT) were used to investigate the effects of alkali treatment with different mass concentrations and different loading directions on the flexibility expression of bamboo, and to evaluate the potential relationship between the structure and flexibility of bamboo. The results showed that in the bamboo samples treated with 15 wt% NaOH, fiber fibrillation and surface thin layer peeling during the fracture process increased the consumption of fracture energy, thereby improving the theoretical tensile strength and bending fracture toughness. Microstructurally, after alkali treatment, the loosening between cells increases the compressible space, leading to a significant prolongation of the plastic stage, especially when loaded from the radial bamboo yellow side (Mode II). When the NaOH concentration reached 25 wt%, the excessive removal of hemicellulose and lignin led to the destruction of the cell wall structure and a decrease in the fiber crystallinity, and the mechanical properties of bamboo were reduced. Therefore, appropriate alkali treatment can maintain the strength of bamboo and improve its flexibility, which is similar to the principle of mercerized cotton. The modified bamboo has application potential in curved components in the transportation field and can meet the requirements of lightweight, flexibility, and environmental protection.